FAM136A depletion induces mitochondrial stress and reduces mitochondrial membrane potential and ATP production - Yushi Otsuka; Masato Yano (FEBS Open Bio)
FAM136A deficiency has been associated with Ménière's disease. However, the underlying mechanism of action of this protein remains unclear. We hypothesized that FAM136A functions in maintaining mitochondria, even in HepG2 cells. To better characterize FAM136A function, we analyzed the cellular response caused by its depletion. FAM136A depletion induced reactive oxygen species (ROS) and reduced both mitochondrial membrane potential and ATP production. However, cleaved caspase‐9 levels did not increase significantly. We next investigated why the depletion of FAM136A reduced the mitochondrial membrane potential and ATP production but did not lead to apoptosis. Depletion of FAM136A induced the mitochondrial unfolded protein response (UPRmt) and the expression levels of gluconeogenic phosphoenolpyruvate carboxykinases (PCK1 and PCK2) and ketogenic 3‐hydroxy‐3‐methylglutaryl‐CoA synthases (HMGCS1 and HMGCS2) were upregulated. Furthermore, depletion of FAM136A reduced accumulation of holocytochrome c synthase (HCCS), a FAM136A interacting enzyme that combines heme to apocytochrome c to produce holocytochrome c. Notably, the amount of heme in cytochrome c did not change significantly with FAM136A depletion, although the amount of total cytochrome c protein increased significantly. This observation suggests that greater amounts of cytochrome c remain unbound to heme in FAM136A‐depleted cells.